MAKNA HIDUP PERSPEKTIF VICTOR FRANKL: KAJIAN DIMENSI SPIRITUAL DALAM LOGOTERAPI - Mukharom, Rohmah Akhirul; Arroisi, Jarman (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2021)
This article aims to reveal the concept of logotherapy of Victor Frankl. This study uses descriptive analysis. First, the concept of logotherapy has three pillars in its philosophical foundation, the freedom of will, in this context every human being free to make choices to determine his own choice and destiny. The will to meaning, which every human being has the desire to have meaning in life. The meaning of life is an awareness of the possibility to realize what is being done at that time which then if successfully fulfilled will produce happiness. Second, in logotherapy, there is a noetic dimension which equivalent to the spiritual dimension, which tends toward the anthropological dimension rather than the theological dimension and does not contain religion. Third, the spiritual logotherapy dimension is different from Sufism. If Sufism spiritual affirms the sharia, then logotherapy departs from human existence. The implications of these differences give to a variety of happiness, both spiritual and physical. Artikel ini bertujuan mengungkap konsep logoterapi yang diformulasikan oleh Victor Frankl. Dengan menggunakan metode deskriptif analitis kajian ini menghasilkan beberapa kesimpulan: pertama, konsep logoterapi memiliki tiga landasan filosofis yaitu, kebebasan berkeinginan (the freedom of will). Dalam konteks ini setiap manusia bebas menentukan pilihan dan nasibnya sendiri. Keinginan akan makna (the will to meaning), yaitu manusia memiliki hasrat untuk memiliki makna hidup. Makna hidup adalah sebuah kesadaran untuk mengetahui apa yang dilakukan saat itu hingga menghasilkan kebahagiaan. Kedua, di dalam logoterapi terdapat dimensi spiritual yang cenderung ke arah antropologis daripada kearah teologis serta tidak mengandung konotasi agama. Ketiga, dimensi spiritual logoterapi berbeda dengan dimenssi dalam tasawuf. Jika para sufi mengafirmasi spiritual pada syariat maka logoterapi berangkat dari human exsistence. Implikasi dari kedua perbedaan tersebut melahirkan ragam kebahagiaan baik kebahagiaan ruhani dan ragawi.